Penggunaan Kaedah B.O.T Dalam Usaha Membangunkan Tanah Wakaf Majoodsaw Pulau Pinang - Hashim Omar, Hydzulkifli; Abu Bakar, Azizi; Shuib, Mohd Sollehudin; Azman Jusoh, Mohd Kamal (Universiti Sains Islam Malaysia, 2024)
Al-Wāqif is individual who donated his property (waqf )to the path of Allah. These properties (waqf)can be rented out to interested parties or used for various economic activities such as agriculture and livestock farming. In cases where the above methods are deemed unsuitable the endowment trustees (nazir) should try to find other alternatives to make the waqf land more productive. The endownment trustees should also explore other avenues to optimize the usage of endowment land under their care. Thus, real estate investment can be used as an alternative to develop the endowment land. Real estate/property investment on waqf assets can be implemented by constructing commercial buildings for rental purpose. The development of these lands will lead to the creation of new waqf assets. This research aim to study the methods used to commerciallydevelop a waqf land (known as wakaf Majoodsaw) that located in center of Geogre Town, Pulau Pinangthat been carried out by the Islamic Religious Council of Pulau Pinang (MAINPP) with Amanah Capital Partners Berhad(ACPB). The Majoodsaw waqfwas successfully developed into anoffice complex known as Menara UMNO Pulau Pinang.